Basal forebrain cholinergic system in the dementias: Vulnerability, resilience, and resistance. Issue 6 (6th August 2021) - Geula, Changiz; Dunlop, Sara R.; Ayala, Ivan; Kawles, Allegra S.; Flanagan, Margaret E.; Gefen, Tamar; Mesulam, Marek‐Marsel
Abstract: The basal forebrain cholinergic neurons (BFCN) provide the primary source of cholinergic innervation of the human cerebral cortex. They are involved in the cognitive processes of learning, memory, and attention. These neurons are differentially vulnerable in various neuropathologic entities that cause dementia. This review summarizes the relevance to BFCN of neuropathologic markers associated with dementias, including the plaques and tangles of Alzheimer's disease (AD), the Lewy bodies of diffuse Lewy body disease, the tauopathy of frontotemporal lobar degeneration (FTLD‐TAU) and the TDP‐43 proteinopathy of FTLD‐TDP. Each of these proteinopathies has a different relationship to BFCN and their corticofugal axons. Available evidence points to early and substantial degeneration of the BFCN in AD and diffuse Lewy body disease. In AD, the major neurodegenerative correlate is accumulation of phosphotau in neurofibrillary tangles. However, these neurons are less vulnerable to the tauopathy of FTLD. An intriguing finding is that the intracellular tau of AD causes destruction of the BFCN, whereas that of FTLD does not. This observation has profound implications for exploring the impact of different species of tauopathy on neuronal survival. The proteinopathy of FTLD‐TDP shows virtually no abnormal inclusions within the BFCN. Thus, the BFCN are highly vulnerable to the neurodegenerative effects of tauopathy in AD, resilient to the neurodegenerative effect of tauopathy in FTLD and apparently resistant to the emergence of proteinopathy in FTLD‐TDP and perhaps also in Pick's disease. Investigations are beginning to shed light on the potential mechanisms of this differential vulnerability and their implications for therapeutic intervention. Abstract : This Review is part of the special issue "Cholinergic Mechanisms" and summarizes the relevance to basal forebrain cholinergic neurons (BFCN) of neuropathologic markers associated with dementias. Available evidence points to early and substantial degeneration of the BFCN in Alzheimer's disease and diffuse Lewy body disease. BFCN are resilient to the neurodegenerative effect of some tauopathies in frontotemporal lobar degeneration (FTLD), such as that is corticobasal degeneration, and they are apparently resistant to the emergence of proteinopathy in FTLD‐TDP and perhaps also in Pick's disease. These findings have important implications for selective neuronal vulnerability and cholinergic based therapies in dementias.